Deuteronomy in Genesis King Abimelech’s Obedience to the Torah (Genesis 20) - Levin, Christoph 1950- (2023)
Gen 20 is the youngest example among the three wife-sister narratives in the Book of Genesis. This time the incident has been narrated according to the rules of the Torah. God reveals to Abimelech in a dream the law of Deut 22,22, and the king, following the precept of Deut 31,10-13, calls his servants together and proclaims it. The servants then fear God, as did the Israelites under Moses. Later editors saw in the narrative an interesting case of “guiltless guilt,” comparable to the problem of collective punishment dealt with in Gen 18,22b-33a. Even later, the narrative was interpreted as evidence of Abraham’s guilt. This allowed one to explain why God put Abraham to such a severe test in Gen 22. In the youngest phase of the narrative’s reworking, Abraham was finally portrayed as a prophet, similar to how Moses was considered a prophet in the late period.